(untitled) (Baghdad Science Journal, 2019)
The varied thermal conductivity (insulation) of silica aerogel with heating for different pH has been investigated, it has been depended on ambient pressure drying method in the preparing silica aerogel samples, also six different pH of samples (1, 2, 3, 7, 8 and 9) were treated under five degree of heating with (50,100,150,200 and 250) ᴼC. This technique is important to test the carry-outs hydrophobic silica to temperature without high-quality material changes in the basic characteristics. The hot-wire technique is used in this work to examine the thermal conductivity, Fourier Transform Infrared Spectroscopy (FTIR) depended to characterize the bonds and their artificial by heating. Results show that the samples affected by heating through decreasing the density leading to obtaining more insulation metal, moreover varied pH is an important role in thermal conductivity. The average thermal conductivity of all aerogel samples in this work is (0.01- 0.0061 mW m-10 C-1) this means that it is still below thermal conductivity for air equals to (0.02257) mW m-10 C-1 . Meanwhile, we concluded that the insulation property of silica aerogel is affected by heat treatment and gives it more thermal insulation property.